If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d + 8whenD = 8 Solving 2d + 8ehnwD = 8 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-8ehnwD' to each side of the equation. 2d + 8ehnwD + -8ehnwD = 8 + -8ehnwD Combine like terms: 8ehnwD + -8ehnwD = 0 2d + 0 = 8 + -8ehnwD 2d = 8 + -8ehnwD Divide each side by '2'. d = 4 + -4ehnwD Simplifying d = 4 + -4ehnwD
| -12-3a=3a+6a | | h(13)=-16t^2+145t+80 | | 3/(5-11i) | | 5+9a+6=6a+8 | | 3/5*84 | | 3/5*60 | | 0.03*.50= | | 0.3*.50= | | 14-4x=1-x-8 | | h=-16t^2+145t+80 | | 20x+8(20)=180 | | h=-16t^2+vt+80 | | -a+14=a+6 | | ln(x)=50 | | 9+-0.4y=4.5+-0.175y | | 7n-n=3n-12 | | 18x+3y+22x+4y=180 | | 20x+8y=180 | | a-17=1-8a | | (-8)+4y=12 | | 5(-2)+3y-5=4 | | (0)+4y=12 | | (8)+4y=12 | | 4y+7=3y-9 | | 3/5*70 | | (2)+y+6=0 | | -15r=60 | | (-8)+y+6=0 | | (-5)+y+6=0 | | 2x-6x=3-5x | | (2)-2y=2 | | -2(0)-4y=4 |